Diversity and Composition of Caddisflies (Insecta: Trichoptera) along an Elevation Gradient in Southeastern Mexico - María Razo-González; Rodolfo Novelo-Gutiérrez; Gabriela Castaño-Meneses; Juan Márquez (Diversity, 2023)
We analyzed the alpha and beta components of male Trichoptera diversity along an altitudinal gradient ranging from 136 to 2432 m a.s.l. by studying five assemblages of adult male caddisflies in five streams of the Sierra de Juárez, Oaxaca, Mexico. Samples were collected with light traps in the “nortes” (February) and rainy (October) seasons of 2016, recording air temperature and relative humidity. The assemblages showed an abundance pattern clearly associated with the rainy season, and a high dissimilarity in their species composition. Species richness and abundance were significantly higher at lower altitudinal levels. The highest alpha diversity was recorded in the Flor de Azahar stream; beta diversity increased with altitude and made an important contribution to gamma diversity. These results suggest that temporal and altitudinal variations affect environmental variables, which influence the structure of Trichoptera assemblages. Temperature was the primary factor determining spatial and temporal distribution patterns of caddisfly assemblages in the study area. However, in the rainy season, this factor explained a smaller proportion of the observed changes. Therefore, it is necessary to evaluate other environmental variables and explore other ecosystems to provide additional evidence on the factors affecting the diversity patterns of the Trichoptera in the Sierra de Juárez.